Influence of Oxygen Content and Microstructure on the Mechanical Properties and Biocompatibility of Ti-15 wt%Mo Alloy Used for Biomedical Applications - Martins, Jose R. S. [UNESP]; Araujo, Raul O. [UNESP]; Donato, Tatiani A. G.; Arana-Chavez, Victor E.; Buzalaf, Marilia A. R.; Grandini, Carlos Roberto [UNESP] (Mdpi Ag, 2014)
The Ti-15Mo alloy has its mechanical properties strongly altered by heat treatments and by addition of interstitial elements, such as, oxygen, for example. In this sense, the objective of this paper is to analyze the effect of the introduction of oxygen in selected mechanical properties and the biocompatibility of Ti-15Mo alloy. The samples used in this study were prepared by arc-melting and characterized by density measurements, X-ray diffraction, scanning electron microscopy, microhardness, modulus of elasticity, and biocompatibility tests. Hardness measurements were shown to be sensitive to concentration of oxygen. The modulus results showed interstitial influence in value; this was verified under several conditions to which the samples were exposed. Cytotoxicity tests conducted in vitro showed that the various processing conditions did not alter the biocompatibility of the material.
Keywords: Ti alloys; microstructure; Rietveld's method; modulus of elasticity; biocompatibility